Knowledge-transfer and self-directed methodologies in university students' learning. Issue 5 (3rd September 2018) - Serdà, Bernat-Carles; Alsina, Ángel
ABSTRACT: This study compared the effectiveness of teaching and learning methodologies based on knowledge transfer (lecture) with approaches that emphasized self-directed learning (Problem-Based Learning [PBL] and Reflective Learning [RL]), in a sample of 230 undergraduate students and eight professors. A mixed-methods study was carried out in a university school of nursing: quantitative methods were used to analyse the outcomes achieved by university students and compared the effectiveness of the various methods based on the students' final examination scores; and qualitative analysis evaluated the factors that affected student learning in each of the three study arms: lecture, PBL and RL. The quantitative results show a better score for RL compared to PBL and the traditional lecture format. Qualitative findings indicate that self-directed methodologies result in higher-quality outcomes in student acquisition of content knowledge. We concluded that simultaneous use of diverse instructional techniques constitutes the best instructional approach. It could be useful in the future to design instruments to evaluate specific skills associated to each technique.